A Casa Escola da Pesca de Outeiro-Belém/PA: para o trabalho e para a liberdade - Silva, Luciane Teixeira da (2022)
The thesis is situated in the field of historiographical research, particularly the History of School Institutions. Its object of study is the Casa Escola da Pesca, a public municipal school located in the insular region of the municipality of Belém, capital of the state of Pará. The school offers Primary and Secondary Education through Youth and Adult Education. It also offers Initial Training courses in Fishing and Aquaculture and Technical courses in Fishing Resources, in each stage, respectively. It uses the Alternation Pedagogy to organize its teaching. The main objective is to retell the history of the Escola da Pesca, taking the Alternation Pedagogy as the common thread. The School is the result of an educational and economic policy that enunciated the valorization of Sustainable Development initiated in the 1990s. Its goal was to include the region of Belém's islands in the economic dynamic whose riverside population lived from the work of artisanal fishing in the productive chain of the fish. The proposed objective for the school was to attend the children of the fishing workers, offering school education and technical training in fishing, taking the Alternation Pedagogy as the means for the integration and the balance between traditional school knowledge and the new work techniques. Their experience of the Alternation Pedagogy is part of the movement and evolution of this pedagogy. Interviews were conducted with students who had graduated from the first classes and also with people involved in the process of creation and installation of the Casa Escola da Pesca. In addition, we used as sources documents produced by and for the school. Fishery workers are part of a population that is mostly illiterate or with an average of three years in school. The training for their work takes place in the families through observation and practice. The creation of a fishing school was the materialization of the desire to have access to Basic Education. The interviews with the graduates revealed that studying at the Escola da Pesca has meant a change in their lives and in their perspective about life, work, and family. Most of the interviewees do not work in fishing, nor do they live in the region of the islands anymore. The school became a space of family, of memories, and of some personal projects.